THE IMAGINATIVE THINKING IN THE STRUCTURE OF NATIVE DESIGN EDUCATION - Креденець, Н. Д.; Семко, А. О.; Шпирало-Заточна, Л. Р. (Art and Design, 2019)
To identify the features, peculiarities and components of imaginative thinking in the context of educational tasks for the professional designer`s training and modern development trends of native design education. Methodology. The research applied following methods: analytical, systematization and generalization. A complex of these related methods provided the authenticity and validity of research result. The peculiarities of designer`s training in the educational sphere in the context of mastering the graphic literacy as an important component of the complex educational disciplines in the structure of design education. The attention is paid to the aspects of development of creative thinking, its internal features and essential characteristics. On the example of still life, different levels of tasks are highlighted, they are facing the students- designers with the purpose of mastering the pictorial component. This initial coursen is introduced of educational process for the professional training and designer`s personal realization of creative abilities. Scientific novelty consists in the definition and coverage of the main components of imaginative thinking, which allowed to outline the ways and methods of formation the graphic literacy in the structure of modern design education. Practical significance.The system of pictorial and graphic tasks can become the basis for further improvement of educational programs “Fundamentals of artistic graphics”, “Painting”. The materials of research can be taken into account in the study of problems in the training of students-designers and teachers of artistic and pedagogical educational institutions.